Competency-and-activity-based Model of Academic Writing - T. S. Putilovskaya (Высшее образование в России)
The article deals with the analysis of academic writing from the viewpoint of activity- oriented and competency-based approaches in present-day linguistic didactics, and with regard to the peculiarity of strategic behaviour concerning mental and speech activity. The author looks at academic writing as a complex type of activity, on the one hand, and the product of this activity, on the other hand. One of the examples of academic writing is a scientific article which is under consideration in the paper. The author describes the principles of working out a competency-based model of a scientific article primarily intended for the teacher and uses it as the basis for working out a step-by-step instruction for writing an article mainly aimed at the student. The model and the instruction can serve as a tool for organizing purposeful training in higher educational institutions and for implementing self-controlled academic activity.